Pengaruh penggunaan ajitein dalam pakan terhadap produksi dan kualitas susu sapi perah - K. P. W. Sunu; Hartutik Hartutik; Hermanto Hermanto (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2013)
The aim of this research was to know the effect of ajitein supplementation as protein source in the ration of dairy cow lactation on milk production and quality. The materials in this research were twelve dairy cows (Friesian Holstein crossbreed). There were 4 treatments, R0= Pennisetum purpureum + concentrate without ajitein + mixed cornbran and soybean husk, R1= Pennisetum purpureum + concentrate with 2 % ajitein (DM concentrate) + mixed cornbran and soybean husk, R2= Pennisetum purpureum + concentrate with 4 % ajitein (DM concentrate) + mixed cornbran and soybean husk and R3= Pennisetum purpureum + concentrate with 6 % ajitein (DM concentrate) + mixed cornbran and soybean husk. The research showed that the treatments did not have significant effect (P>0.05) on dry matter intake (DMI), organic matter intake (OMI), crude protein intake (CPI), milk quality, milk production and Average Daily Gain (ADG). The highest DMI was found on R1 (3.55 % of body weight), OMI was found on R1 (87.06 % of DMI), CPI was found on R1 (14.25 % of DMI), milk production was found on R1 (12.58 kg/head/day) with an increasein milk production approximately 1.32 kg/head. The highest milk quality was found on R2 with 1.0259 kg/l density, 4.61% of fat, 8.46% of solid non fat (SNF), and 13.07% of total solid (TS). The highest ADG was found on R3 1038.10 g/head/day. This meant that ajitein supplementation up to 6% as iso protein on dairy cow ration did not give any effect to milk production, but the use of ajitein could lower the price per kg of feed to produce milk.   Keywords: ajitein, dairy cow, feed intake, milk production, milk quality, ADG